Poultry Science, Chicken Culture : A Partial Alphabet - Squier, Susan Merrill (Book collections on Project MUSE., 2011)
Poultry Science, Chicken Culture is a collection of engrossing, witty, and thought-provoking essays about the chicken-the familiar domestic bird that has played an intimate part in our cultural, scientific, social, economic, legal, and medical practices and concerns since ancient Egypt, Greece, and Rome. Organized as a primer, the book reaches beyond narrow disciplines to discover why individuals are so fascinated with the humble, funny, overlooked, and omnipresent chicken. A combination of personal passion and surprising scholarly information, it will change forever the way you think.